THE INTERACTION OF WHEEL SETS AND RAILS WAY - Ilman, V. M.; Skalozub, M. V. (Science and Transport Progress, 2008)
This article offers the methods of calculation of the start points of contact during wheel set-rails family interaction. The states of wheel set are investigated; the types of possible specific wheel set states, turning-over of rolling stock elements and their derailment are determined.